Contribution of Soluble Forms of Programmed Death 1 and Programmed Death Ligand 2 to Disease Severity and Progression in Systemic Sclerosis. Issue 9 (1st August 2017) - Fukasawa, Takemichi; Yoshizaki, Ayumi; Ebata, Satoshi; Nakamura, Kouki; Saigusa, Ryosuke; Miura, Syunsuke; Yamashita, Takashi; Hirabayashi, Megumi; Ichimura, Yohei; Taniguchi, Takashi; Asano, Yoshihide; Shimizu, Hisashi; et al.
Abstract : Objective: To determine the function and serum levels of soluble forms of programmed death 1 (sPD‐1) and one of its ligands, soluble PD ligand 2 (sPD‐L2), in patients with systemic sclerosis (SSc) and in a mouse model of topoisomerase I (topo I)–induced SSc. Methods: Serum levels of sPD‐1 and sPD‐L2 in 91 patients with SSc were examined by enzyme‐linked immunosorbent assay (ELISA). Expression of PD‐1 and PD‐L2 on T cells, B cells, and macrophages was quantified by flow cytometry. The effects of blockade of PD‐1 and PD‐L2 were analyzed by microfluidic ELISA (micro‐ELISA), a technique that can measure very low amounts of cytokines. In addition, the effects of sPD‐1 and sPD‐L2 on disease progression were assessed in mice with topo I–induced SSc. Results: Serum levels of sPD‐1 and sPD‐L2 were elevated in patients with SSc and correlated with the extent of fibrosis and immunologic abnormalities. Expression levels of PD‐1 and PD‐L2 were significantly elevated on SSc T cells, B cells, and macrophages. Micro‐ELISA analysis of serum samples from patients with SSc showed that PD‐L2 high B cells had higher levels of interleukin‐10 (IL‐10) production compared with PD‐L2 low B cells, indicating that PD‐L2 acts as a regulator of T cell cytokine production via cognate interactions with T cells and B cells. In mice with topo I–induced SSc, production of IL‐10 by topo I–specific B cells in cultures with T cells and topo I protein was significantly higher than that by conventional B cells, and intraperitoneal injection of recombinant chimeric PD‐1‐Fc and PD‐L2‐Fc canceled these enhanced effects. Conclusion: These results suggest that sPD‐1 and sPD‐L2 contribute to disease development in SSc via the regulation of cognate interactions with T cells and B cells.